Specific secretory phase endometrial leukocytes of women with two and more consecutive idiopathic abortions are not significantly different from healthy controls - Bohlmann, Michael K.; Luedders, Doerte W.; Strowitzki, Thomas; Wolff, Michael von (Archives of gynecology and obstetrics, 2010)
To analyze concentrations of endometrial leukocytes in patients with idiopathic-repeated abortions.
Erstmals am 15. Juli 2009 online veröffentlicht
Gesehen am 02.02.2023